Perlindungan Hukum Bagi Pembeli Tiket Konser Musik Serasa Nada di Yogyakarta yang Dibatalkan Sepihak - Erica S, Patricia Pascalina; Mandiana, Sari; Susiawati Achmad, Andyna (UNES Law Review, 2024)
This research discusses the unilateral cancellation of concerts by organizers at Serasa Nada music concerts in Yogyakarta. This research uses Normative Juridical research type in which the processing of legal materials is done through literature study. This study aims to analyze the legal protection of Serasa Nada concert ticket buyers in Yogyakarta who were unilaterally canceled by the organizer. The results showed that for the cancellation of the Serasa Nada music concert in Yogyakarta there are legal consequences that occur, namely default. The legal consequences of default are penalties or sanctions in the form of paying losses, canceling the agreement, transferring risks and paying court costs. In addition, because it uses an electronic platform, the rules of Article 17 of the ITE Law and Article 18 paragraph (1) of the ITE Law jo. Article 46 paragraph (1) PP 71/2019 and the organizer is responsible according to Article 21 paragraph (2) letter c of the ITE Law. Legal efforts that can be made by buyers of Serasa Nada concert tickets are to file a civil lawsuit, namely a lawsuit for default in Article 1267 of the Civil Code and because concert ticket sales use a platform which is a form of electronic transaction, ticket buyers can file a lawsuit in Article 35 jo. Article 38 of the ITE Law. In addition, a criminal lawsuit can be filed in Article 28 paragraph (1) jo. Article 45 paragraph (2) of the ITE Law.